Description of HbA1c Levels in Patients with Diabetes Mellitus and Hypertension in Bengkulu City - Abelia Abelia; Heru Laksono (Jurnal Fatmawati Laboratory & Medical Science, 2026)
Background: Diabetes mellitus (DM) and hypertension are two non-communicable diseases that are closely related and simultaneously increase the risk of serious cardiovascular complications. Long-term uncontrolled blood glucose levels may cause vascular damage, trigger insulin resistance, and contribute to hypertension. One important parameter used to assess long-term glycemic control is HbA1c, which reflects average blood glucose levels during the previous two to three months. Objective: To describe HbA1c levels among diabetes mellitus patients with hypertension in the working areas of Telaga Dewa and Jembatan Kecil Public Health Centers, Bengkulu City, in 2025. Methods: This study used a descriptive design with a cross-sectional approach. The sample consisted of 30 respondents selected using a total sampling technique. Data were collected through HbA1c examinations using the SD Biosensor Standard F device and interviews regarding age, gender, and duration of illness. A descriptive cross-sectional study was conducted among 30 patients with diabetes mellitus and hypertension selected using total sampling. Results: Most respondents (76.7%) had uncontrolled HbA1c levels (≥7%). The majority of respondents were female (70.0%), aged ≥50 years (86.7%), and had suffered from diabetes mellitus for more than 5 years (60.0%). Conclusion: Blood glucose control among diabetes mellitus patients with hypertension remains low, particularly among elderly and female patients.